2020
DOI: 10.1016/j.xphs.2019.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ Receptor Activation by Human Monoclonal Antibody Aggregates

Abstract: Protein aggregates are a potential risk factor for immunogenicity. The measurement, characterization, and control of protein aggregates in drug products are indispensable for the development of biopharmaceuticals, including therapeutic mAbs. In this study, Fcg receptor (FcgR)-expressing reporter cell lines were used to analyze the FcgR-activation properties of mAb aggregates. Comparison of aggregates of mAbs harboring different IgG subclasses revealed that the FcgR-activation profiles of the mAb aggregates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…FcgRIa, IIa, and IIIa activation was assessed using Jurkat cells expressing each FcgR via NFAT-driven expression of the luciferase gene. 6,29 The Jurkat/FcgRIa/NFAT-Luc cells, Jurkat/FcgRIIa/NFAT-Luc cells, and Jurkat/FcgRIIIa/NFAT-Luc cells (5 Â 10 4 cells/well) suspended with Opti-MEM I Reduced Serum Media (Thermo Fisher Scientific) were seeded in a 96-well plate with serially diluted agitated sample. After incubation for 5 h at 37 C in 5% CO 2 , the luciferase activities were determined using the ONE-Glo Luciferase Assay System (Promega, Cat #E6110) on an Ensight Multimode Plate Reader (PerkinElmer).…”
Section: Fcgrs Reporter Cell Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…FcgRIa, IIa, and IIIa activation was assessed using Jurkat cells expressing each FcgR via NFAT-driven expression of the luciferase gene. 6,29 The Jurkat/FcgRIa/NFAT-Luc cells, Jurkat/FcgRIIa/NFAT-Luc cells, and Jurkat/FcgRIIIa/NFAT-Luc cells (5 Â 10 4 cells/well) suspended with Opti-MEM I Reduced Serum Media (Thermo Fisher Scientific) were seeded in a 96-well plate with serially diluted agitated sample. After incubation for 5 h at 37 C in 5% CO 2 , the luciferase activities were determined using the ONE-Glo Luciferase Assay System (Promega, Cat #E6110) on an Ensight Multimode Plate Reader (PerkinElmer).…”
Section: Fcgrs Reporter Cell Assaymentioning
confidence: 99%
“…24 Tada et al have described the detailed FcgRs activation properties evoked by agitation-induced antibody aggregates. 6 These observations have led us to hypothesize that the affinity of aggregated antibody-SO complexes for FcgRs could be increased by Fc-multivalent binding. 25,26 Despite there have been several reports indicating that the aggregated protein-SO complexes could exhibit higher immunogenicity, 18,27,28 the FcgRs activation capability of them remains unclear, limiting our understanding of their immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Fc duplication (or tandem-Fc) or multiplication, whereby multiple Fcs are linked within one IgG1 molecule, has been shown to augment FcγR binding avidity and increase ADCC and ADCP [ 56 , 57 , 58 , 59 ] ( Figure 2 C). A theoretical safety concern for Fc multiplication strategies is the fact that natural antibody oligomerization may result in unwanted immune activation [ 60 ]. However, studies have reported minimal in vitro aggregation and no in vivo adverse events so far [ 57 , 59 ].…”
Section: Fc Engineering To Enhance Fc-effector Functionsmentioning
confidence: 99%
“…Indeed, Polumuri et al showed no implication of TLRs, including TLR2 and TLR4, in the activation of HEK293 cells expressing TLRs in response to IVIG aggregates (50). More recently, the use of other reporter cell models showed that antibody aggregates induced FcγRs activation, mainly FcγRIIa and FcγRIIIa; however, they did not activate TLRs (51). Taken together, all these results indicate that the activation of PBMCs in response to aggregated antibodies is multifactorial, through the potential engagement of multiple receptors.…”
Section: Interaction Of Antibody Aggregates With Peripheral Blood Monmentioning
confidence: 99%
“…This strongly suggests that these aggregates would be internalized by either phagocytosis or macropinocytosis; however, no data has yet confirmed this FIGURE 1 | Antibody aggregates act as danger signals for innate immune cells. [1] Aggregates interact with antigen-presenting cells (APCs) via Fcγ receptors (FcγRs) or toll-like receptors (TLRs) (47,(49)(50)(51). [2] Aggregates induce the phosphorylation of intracellular signaling kinases (50,55).…”
Section: The Role Of Antibody Aggregates In the Initiation Of A Specimentioning
confidence: 99%